ANALISIS ASAL DAERAH DAN PEKERJAAN WALI MAHASISWA SISTEM IINFORMASI UNIVERSITAS ISLAM INDRAGIRI ANGKATAN 2023 MENGGUNAKAN POWER BI - IBN, khairul khatimah (PT. ZIVANA CENDEKIAWAN BANGSA, 2025)
This research aims to analyze the regional origin and job profile of the guardians of Indragiri Islamic University Information Systems students class of 2023 using the Power BI data visualization tool. The data used in this research was obtained from a survey conducted on these students in 2023. The analysis methods used include data segmentation, creating interactive visualizations, and modeling to describe the characteristics of the students' guardians' residences and workplaces. The results showed that there was significant variation in the residence of student guardians, and the majority came from outside the area. Apart from that, the analysis also reveals the variety of jobs held by student guardians, ranging from professional to entrepreneurial. Data visualization using Power BI facilitates a better understanding of these patterns, highlighting relevant trends and differences within groups.